2020
DOI: 10.3390/biomedicines8090317
|View full text |Cite
|
Sign up to set email alerts
|

Well-Defined Construction of Functional Macromolecular Architectures Based on Polymerization of Amino Acid Urethanes

Abstract: Polypeptide synthesis was accomplished using the urethane derivatives of amino acids as monomers, which can be easily prepared, purified, and stored at ambient temperature without the requirement for special precautions. The urethanes of amino acids are readily synthesized by the N-carbamoylation of onium salts of amino acids using diphenyl carbonate (DPC). The prepared urethanes are then efficiently cyclized to produce amino acid N-carboxyanhydrides (NCAs). Thereafter, in the presence of primary amines, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Secondly, the storage of NCA is very difficult, due to its sensitivity to moisture and heat. Thus, alternative monomers for the large-scale synthesis of polypeptides have been extensively studied over the years [12,13]. However, there are two main drawbacks that limit the use of NCA on an industrial scale.…”
Section: Ring-opening Polymerization (Rop) Of α-Amino Acid N-carboxy ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the storage of NCA is very difficult, due to its sensitivity to moisture and heat. Thus, alternative monomers for the large-scale synthesis of polypeptides have been extensively studied over the years [12,13]. However, there are two main drawbacks that limit the use of NCA on an industrial scale.…”
Section: Ring-opening Polymerization (Rop) Of α-Amino Acid N-carboxy ...mentioning
confidence: 99%
“…Commonly, three different synthetic pathways are used to prepare peptides in the laboratory: via the polymerization of amino acid N-carboxyanhydrides (NCAs) [6,9,10], amino acid N-thiocarboxyanhydrides (NTAs) [11,12], and N-phenoxycarbonyl amino acids (NPCs) [13]; via various stepwise coupling reactions of α-amino acids, such as during solid phase peptide synthesis (SPPS) [14]; or via recombinant DNA techniques for expressing peptides in microorganisms [14]. Polypeptides that are synthesized through SPPS have controlled primary sequences and can fulfill certain functionalities, but it is difficult to create high molecular weight polypeptides above 100 residues, due to the inevitable side reactions [15].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] The living polymerizations of urethane derivatives of amino acids including NPCs were first reported by Takeshi Endo and co-workers. [11][12][13][14][15] This method offers precise control over molecular weights and achieves narrow dispersity of polymers. The NPC polymerization takes place at temperatures between 60 and 80 °C, using N,N-dimethylacetamide (DMAc) as a solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of cysteine blocks can solidify the initially loosely associated capsule walls by forming networks of disulfide bonds (Figure 1). The triblock peptides are synthesized by polymerization of activated urethane derivatives (UDs) of amino acids as reported by Endo et al [11] Their chemical structures are identified using 1 H-NMR, MALDI-TOF MS, and gel permeation chromatography (GPC). The morphology and size distribution of the PFD-filled capsules are investigated with Atomic Force Microscopy (AFM) and particle tracking via Video Microscopy (VM).…”
Section: Introductionmentioning
confidence: 99%